HUBUNGAN STRATEGI PEMBELAJARAN GURU DAN KEAKTIFAN SISWA DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SENI BUDAYA DI SMA NEGERI 1 LEMBAH GUMANTI - IRMA SURYAWARDI, Dr. Ramalis Hakim,M.Pd, Dra. Jupriani, M.Sn (Serupa The Journal of Art Education, 2014)
The purpose of this study is to know how many relationship of the Teacher Learning Strategies and Students activity to Learning Outcome from subjek of Art in SMAN 1 LEMBAH GUMANTI. This study is a descriptive correlational. The primary source of data are data obtained directly from the respondents, and taking from filling some questionnaire of 36 students of class XI IPA 1 and 2 are made to the sample, while the secondary source of data are student learning outcomes, which obtained from teachers of Arts. Data were analyzed using SPSS ( Statistic Product and Service Solutions ) version 16.0. Result of data processing: ( 1 ) The first hypothesis , the results of t-test analysis obtained t ( count ) are 4.083 while t ( table ) are 2.032, that means there are significant relationship between variables with r2 ( r square ) are 0.574 so that the percentage of relationship from the teachers learning strategy with the learning outcomes are 32.94 %. (2) The second hypothesis , the results of t-test analysis obtained t ( count ) are 3.451 while t ( table ) are 2.032, that mean there are significant relationship between variables with r2 ( r square ) are 0.509 so that the percentage of relationship from student activity with the learning outcomes are 25.90 %. ( 3 ) The third hypothesis, from the analysis of F, finding F ( count ) are 12.674 while F ( table ) amounted to 3.285, that means there are significant relationship of the each other from variables with R2 ( R square ) is 0.659, so the relationship teacher learning strategies and student activity with the learning outcomes of 43.42 %, and than the hypothesis of this study have been accepted and verified. Kata Kunci : Strategi Pembelajaran, Guru, Keaktifan, Siswa, Hasil Belajar